2010
DOI: 10.1007/s10096-010-1094-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of gastroenteritis in hospitalised children: prospective survey during a 2-year period in a Parisian hospital, France

Abstract: International audienceRotavirus is recognised as the most important agent of severe acute gastroenteritis (AGE) in young children. In a 2-year prospective survey, we investigated the epidemiology and clinical features of the viral and bacterial pathogens in children hospitalised for AGE. The study was performed in a Parisian teaching hospital from November 2001 to May 2004. Clinical data were prospectively collected to assess the gastroenteritis severity (20-point Vesikari severity score, the need for intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
38
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 55 publications
12
38
2
5
Order By: Relevance
“…In recent studies, it was calculated that the rotaviruses cause approximately 111 million episodes of the gastroenteritis requiring only home care, 25 million clinical visits, 2 million hospitalizations and 352,000-592,000 deaths in children aged <5 years old worldwide, each year (Parashar et al, 2003). The frequency of rotavirus detection in this study (27.85%) was in keeping with numerous other studies conducted in developing and developed countries that have reported rotavirus to be responsible for between 14 and 50% of all cases of gastroenteritis (Nelson et al, 2008;Lacroix et al, 2010;Mladenova et al, 2010;Jere et al, 2011;Lorrot et al, 2011). Extensive molecular epidemiological studies globally have indicated that G1 is the most common circulating genotype.…”
Section: Discussionsupporting
confidence: 78%
“…In recent studies, it was calculated that the rotaviruses cause approximately 111 million episodes of the gastroenteritis requiring only home care, 25 million clinical visits, 2 million hospitalizations and 352,000-592,000 deaths in children aged <5 years old worldwide, each year (Parashar et al, 2003). The frequency of rotavirus detection in this study (27.85%) was in keeping with numerous other studies conducted in developing and developed countries that have reported rotavirus to be responsible for between 14 and 50% of all cases of gastroenteritis (Nelson et al, 2008;Lacroix et al, 2010;Mladenova et al, 2010;Jere et al, 2011;Lorrot et al, 2011). Extensive molecular epidemiological studies globally have indicated that G1 is the most common circulating genotype.…”
Section: Discussionsupporting
confidence: 78%
“…In general, the severity of sapovirus gastroenteritis is milder than that for rotavirus and norovirus (Table 5) (185,186,191). Gastroenteritis symptoms are usually self-limiting, and patients usually recover within a couple of days; however, the symptoms, severity, and duration of disease are dependent on the individual, and sapovirus infection sometimes leads to hospitalization (22,152,167,(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209). Mortality is rare, but it was reported from outbreaks that occurred in a long-term-care facility for the elderly (104).…”
Section: Symptoms and Severity Of Diseasementioning
confidence: 99%
“…In a separate study from France, astroviruses were detected in 1.5 % cases of children hospitalized with acute gastroenteritis [21]. In Saudi Arabia, astrovirus associated diarrhoea cases were reported in 1.5 % of pediatric population and faecal specimens were characterized for genotype by using molecular methods (PCR, RT-PCR, and RFLP) [35].…”
Section: Astrovirus Detection In Various Settingsmentioning
confidence: 99%